An evaluation of novel AMP2-coated electrospun composite scaffolds for intraoral bone regeneration: a proof-of-concept in vivo study - Slavin, Blaire V.; Wu, Shangtao; Sturm, Savanah R.; Hwang, Kevin K.; Almada, Ricky; Mirsky, Nicholas A.; Nayak, Vasudev Vivekanand; Witek, Lukasz; Coelho, Paulo G. (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundAlveolar ridge preservation by guided bone regeneration (GBR) is a surgical procedure that can be performed prior to implant placement to increase the likelihood of survival. Autogenic, allogenic, or xenogeneic derived bone (particulate graft) are frequently placed in conjunction with a barrier membrane for GBR; however, advancements in tissue engineering have led to the development of promising synthetic alternatives. Fiber-based scaffolds exhibit high surface-to-volume ratio and thereby improve cellular adhesion, reduce the likelihood of dehiscence and poor bone regeneration often associated with poorly immobilized particulate graft. This study aimed to evaluate the in vivo performance of a novel electrospun composite scaffold coated in a recombinant variant of human bone morphogenetic protein-2 (OsteoAdapt) relative to a porcine-derived xenograft. Further, it sought to determine if OsteoAdapt would remain within the defect without a membrane in place, as this is not feasible with the particulate xenograft currently used in clinical practice.MethodsFour-walled mandibular defects were created in each adult beagle dog (n = 4 defects per dog; n = 4 dogs for a total of 16 defects). Each defect received one of three experimental (test) groups: (i) OsteoAdapt without membrane (OA), (ii) OsteoAdapt with porcine membrane (OA/ZM), (iii) OsteoAdapt mixed with porcine particulate xenograft (Zcore™) with porcine membrane (OA/P/ZM) and compared to a positive control - Zcore™ with porcine membrane (CTRL). After 4-weeks in vivo, bone regeneration was assessed through qualitative volumetric reconstruction, qualitative and quantitative histological analyses.ResultsHistomorphometric measurement of bone regeneration (% bone) within the region of interest revealed no significant differences between OA, OA/ZM, or OA/P/ZM in comparison to the CTRL at 4-weeks (p = 0.086, p = 0.218, and p = 0.806, respectively). Similarly, evaluation of soft tissue presence (% soft tissue) indicated no significant differences between experimental groups OA, OA/ZM, or OA/P/ZM relative to the CTRL (p = 0.341, p = 0.679, p = 0.982, respectively). However, qualitative analysis of the histological micrographs demonstrated advanced bone healing characterized by an abundance of nucleation sites for regeneration to occur in defects treated with OA relative to the CTRL. Bone overgrowth beyond the limits of defect borders was observed in groups treated OA/ZM and OA/P/ZM. In contrast to the treatment groups, minimal woven bone was visualized in the CTRL group.ConclusionCompared to defects treated with porcine-derived particulate and barrier membrane (CTRL), defects filled with OA exhibited bone regeneration throughout the defect, with bone overgrowth when covered by a barrier membrane at 4-weeks in vivo. This suggests that the novel combination of AMP-2 and a bioceramic/synthetic polymer-based electrospun scaffold is a suitable candidate for GBR procedures, without a barrier membrane to secure its place within a defect.